(untitled) (Al-Academy, 2026)
Arts of all kinds are a fertile source of inspiration for creating new formative dimensions for decoration. By studying their artistic features and analyzing the vocabulary of their formative construction, the artist can create an intellectual reserve that enables him to translate, reformulate, and employ them in a new way in his artistic proposals. Integrating artistic motifs is a contemporary aesthetic trend that enriches artistic values and opens up broad creative horizons. This integration creates a rich artistic dialogue between diverse decorative styles belonging to different environments, cultures, and time periods. The motifs of Saudi Sadu weaving represent a unique artistic identity, as their compositions include symbols and social and aesthetic connotations that express the culture and values of Bedouin tribes. Artistic pendants are one of the most prominent forms of applied arts that combine aesthetic and functional value, as they are used as decorative media that give spaces an artistic character and a distinct identity. The research aims to: 1. Introduce formative dimensions from William Morris’s motifs and Sadu patterns and employ them in artistic pendants to develop small projects. 2. Measure the degree of acceptance by specialists of pendant designs developed from the formative dimensions of William Morris’s motifs and Sadu patterns to develop small projects. 3- Measuring the degree of consumer acceptance of the designs of the new pendants from the formative dimensions of the artist William Morris’s decorations and “Sadu” engravings to develop small projects.